(untitled) (مجلة ديالى للبحوث الانسانية, 2022)
Schiff bases were prepared envolving the reaction of 3-acetylindol with bromine to give α-bromo acetylindol.The reaction of the later with urea,acetamide and thiourea afforded substituted oxazole and thiozole respectively. The reaction of substituted thiozole with different aldehydes gave new derivatives of Schiff bases (imines)